Modelling survival and factors associated with HIV-infected and -uninfected patients of prostate cancer at the University Teaching Hospital, Lusaka, Zambia - Kelvin Mwangilwa; Moses Mwale; Susan Citonje; Michael Vinikool; Patrick Musonda (Taylor & Francis Group, 2023)
Abstract: Incidence and mortality rates as a result of prostate cancer (PCa) remain high in the world, especially among the population of people living with human immunodeficiency virus (HIV), with high mortality mainly in Africa. Therefore, this study determined the survival rates among HIV-positive compared to HIV-negative PCa patients and factors associated with mortality. This was a retrospective cohort study of PCa patients at Cancer Disease Hospital in Lusaka, Zambia, for the observational period of 5 years. Patients were followed up using mobile phone calls to understand the time contributed from time at diagnosis to death. Patients who were lost to follow-up were censored at the date of last follow-up at the hospital. A total of 662 cases were evaluated. The total person time at risk was 7,548 months. After 5-year follow-up, there were 290 (43.8%) deaths, suggesting crude mortality rate of 430 per 10,000 persons per year. The overall median survival time was 16 months. In an adjusted model, the following variables had a statistically significant effect on the hazard of death: 1-year increase in age, increased the hazard of death by about 3%, AHR: 1.03 (95% CI: 1.02, 1.05, p = 0.001); HIV-positive patients had reduced hazard of death by about 41%, AHR: 0.59 (95% CI: 0.44, 0.79, p = 0.001); Gleason score (GS) less than or equal to 8, the patients with GS greater than 8 had increased hazard of death by about 43%, AHR: 1.43 (95% CI: 1.27, 1.59, p = 0.001); those on hormonal therapy had reduced hazard of death by about 28% AHR: 0.72 (95% CI: 0.54, 0.94, p = 0.018) and those presented with tumour stages I and II had reduced hazard of death by about 82%, AHR: 0.18 (95% CI: 0.04, 0.78), p = 0.021). Survival from death following whether a patient was HIV-positive or not was more in the HIV-positive compared to HIV-negative and this could be due to high GS in the HIV-negatives compared to HIV-positives and late-stage diagnosis of the disease at the hospital especially among the HIV-negative patients as evidenced by the increased hazard of death compared to HIV-positives. Therefore, medical check-up such as screening for PCa which leads to early diagnosis of the cancer must be encouraged in men.